Thank you, Jeeves - Wodehouse, P. G. (Pelham Grenville), 1881-1975 (Wodehouse, P. G. (Pelham Grenville), 1881-1975. Collector's Wodehouse., 2003)
Bertie Wooster's newfound enthusiasm for the banjolele results in his eviction from his apartment and having to take notice from his hitherto devoted manservant, Jeeves. Repairing to the country with his banjolele and new valet, Brinkley, Bertie soon finds himself in no shortage of trouble. A visit to an American yacht ends with him locked in a stateroom by a prospective father-in-law. Bertie escapes to his cottage only to find an intoxicated Brinkley who chases Bertie with a carving knife into his bedroom, then sets the cottage ablaze. Only Jeeves - brilliant Jeeves - can set Bertie's world aright.